OLIMPIADE TOKYO 1964 SEBAGAI MOMENTUM PERUBAHAN JEPANG - Arsi Widiandari (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
Globalization, one of which is characterized by advances in the field of communication and information technology, one side does provide many conveniences, but on the other hand there are negative impacts caused by this research aims to analyze the importance of Pancasila values as a paradigm for cultural development in the global era. This research is qualitative research in the field of philosophy. The method used in this study is synthesis analysis with methodical elements of interpretation. The formulation of the results in this study is that globalization is an era in which there is a process of internationalization, namely the unification of the world that produces a global culture called a culture without space boundaries. Therefore, in the development of culture in Indonesia, it must remain oriented towards the personality of the nation, which is based on Pancasila. Culture must be developed in accordance with human nature. Cultural development based on the values of Pancasila as a paradigm will form a society oriented towards the goal of uplifting human dignity and dignity. Pancasila as a cultural paradigm means Pancasila as a normative source for increasing humanization in the cultural field